Formulasi dan Uji Aktivitas Antioksidan Sediaan Lip Balm Ekstrak Etanol Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) dengan Metode DPPH - Nur Jannah; Bangkit Riska Permata; Kharisma Jayak Pratama (Journal of Innovative and Creativity, 2026)
The lips are one of the facial areas that are prone to dryness and damage due to environmental exposure and free radicals. Therefore, the use of lip balm containing natural antioxidants is needed to protect and maintain lip health. Pandan wangi leaves (Pandanus amaryllifolius Roxb.) are known to contain bioactive compounds such as flavonoids, tannins, alkaloids, and saponins which have antioxidant potential. This study aimed to formulate a lip balm containing ethanolic extract of pandan wangi leaves and to evaluate its antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. Pandan wangi leaves were extracted using 70% ethanol by maceration. The obtained extract was subjected to standardization, phytochemical screening, and antioxidant activity testing. Furthermore, the extract was formulated into lip balm preparations with extract concentrations of 1%, 3%, and 5%. The resulting lip balm formulations were evaluated for their physical quality, including organoleptic properties, homogeneity, pH, spreadability, and adhesion. The antioxidant activity of the lip balm preparations was determined using the DPPH method and compared with a commercial lip balm as a reference. showed that the ethanol extract of pandan wangi leaves exhibited very strong antioxidant activity with an IC₅₀ value of 7.87 ppm. All lip balm formulations met the requirements for good physical quality.